Telecommunications Systems and Technology - Barnes William E.; Khader Michael (Prentice Hall, 2000)
This book provides a clear and complete introduction to the operations common to many telecommunications systems. Basic Concepts, Digital Transmission, T1/ T3 Applications and Subscriber Loop Carrier Systems, Switching Systems, Computer Telephony and Applications, Modem Communications, Protocols and Standards, Broadband ISDN and ATM, Basics of Local Area Networks, Internet Working with TCP/ IP, Introduction to Wireless Communications, Multimedia Communications, Selected Bibliography, Glossary, Acronyms, Index.